“A Clarion Call To Real Patriots The World Over”: The Curious Case of theKu Klux Klan of Kanada in New Brunswick during the 1920s and 1930s - Cline, Tyler (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2019)
The Ku Klux Klan movement in New Brunswick in the 1920s and 1930s was part of a wave of anti-Catholicism in the Northeast. The supposedly American organization’s connections with local Protestants, such as the Orange Order and Conservative politicians, coupled with New Brunswick’s long history of anti-Catholicism, indicate that the Klan’s nativism was not foreign to the province. Instead, it was part of a region-wide response to a thriving Catholic population that challenged the Protestant, anglophone milieu. The Klan’s transnational “Patriotic-Protestantism” rejected bilingualism and Catholic participation in the political sphere while promoting traditional Anglo-Saxon values and Protestant morality.